Potential of gathot (fermented cassava) from livestock feed to analog rice. Issue 1 (November 2021) - Ratnaduhita, A; Pratama, Y; Nuhriawangsa, A M P; Pramono, Y B; Kartikasari, L R
Abstract: The objective of this research was to analyze the potential of gathot as an analog rice ingredient with the addition of red bean CMC as a binder, according to water absorption value, crude fiber content, and aftertaste by hedonic test. This study consisted of 4 treatments, and each treatment was repeated 5 times. The treatment was the addition of CMC in the manufacture of analog rice made from gathot flour and red bean flour with a level of 0; 1; 2; 3%. The test includes water absorption, crude fiber content, and aftertaste with a hedonic test. The data were analyzed by Completely Randomized Design (CRD) and processed using SPSS 23.0. Gathot's analog rice showed water absorption 49.37%, crude fiber content 0.57 g/mL, and aftertaste 3.24. Gathot's analog rice with the addition of red bean flour and CMC as binder influences the water absorption value and crude fiber content. The optimal concentration of CMC in gathot's analog rice is 1%, with the water absorption value of 163.37% and crude fiber content of 5.37%.